Strategi Peningkatan Cakupan Terapi Pencegahan Tuberkulosis (TPT) - Atzmardina, Zita; Princess Ruth Pricillia; Olivia Larissa; Rizky Audryan; Miranda Angtoni (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis, transmitted via droplets from coughing or sneezing. TB mainly affects the lungs but may spread to other organs (Extrapulmonary TB). In the Puskesmas working area, 166 TB cases were recorded. This activity aimed to increase the number of recipients of Tuberculosis Preventive Therapy (TPT) among individuals with close contact history. Problem identification used Blum’s Paradigm, with data collected through a mini survey. Priority issues were determined using the non-scoring Delphi method, and root causes were analyzed via a Fishbone diagram. Evaluation applied the PDCA cycle and systems approach. Lifestyle factors were identified as the main contributor to low TPT coverage. After implementing counseling as an intervention, results showed positive outcomes: 50% of residents and 71% of health cadres experienced improved knowledge. The intervention is considered successful and is expected to enhance TPT coverage sustainably.